Thermal behavior of external-insulated cold-formed steel non-load-bearing walls exposed to different fire conditions. (June 2020) - Chen, Wei; Jiang, Jian; Ye, Jihong; Zhao, Qingyang; Liu, Kun; Xu, Changzheng
Abstract: An external-insulated cold-formed steel (CFS) wall is a potential configuration that overcomes the disadvantage of cavity insulation in the fire performance of such walls and can meet the sound and thermal insulation requirements for building structures by increasing the thickness of insulation material. This paper conducted eight mid-scale non-load-bearing fire experiments on external-insulated wall specimens. Four different fire conditions were tested, including ISO 834 fire, external fire, hydrocarbon fire and a typical realistic design fire. A quasi-steady heat transfer state was identified at the final stage of external fire exposure. The effect of substituting the cavity insulation with external insulation on the fire performance is discussed by comparison with the previous fire experiments on cavity-insulated CFS walls. The results show that external insulation is a more reasonable configuration than cavity insulation for improving the fire resistance of CFS walls. In addition, two types of stud buckling, which include the local buckling of the whole stud section and local buckling of stud hot flange and adjacent web, were identified for non-load-bearing walls in fire, and the corresponding cause and conditions were described. In addition, to achieve high efficiency in the thermal performance modeling of CFS walls in fire, a quick and simplified calculation method was developed to get the temperature profile of steel frame based on a one-dimensional finite difference method. Moreover, an unexposed surface temperature of 900 °C was recommended as the criterion to predict the falling-off of the fire-side face-layer gypsum plasterboards of CFS walls in the heat transfer modeling.